Contribuições de Paulo Freire para se pensar o uso das tecnologias na educação - Gusmão, Márcia Jardim (2022)
This project seeks to analyze the possible contributions of Paulo Freire to think the presence of (new) technologies in education in the present context. The concern of the author with pragmatism and technicality in education guide the reflections about the risks of a purely technical education that demands quick decisions and commits the critical formation and autonomy developing of the student. He was attentive to the needs of the schools of adapting themselves to these accelerated changes and the dangers of deepening of the already serious problems in the current educational system, which he calls banking education, antidialogic and based on transmission, that does not promote the access to knowledge and transformation of reality. Freire understands education as a political act. He concerns about subjects placed at the margins of historical process and the valorization of their cultures considered inferiors. The methodology used on the realization of this project was the bibliographic research, analyzing the conceptual categories of Paulo Freire to think in a libertarian education, such as: dialogical perspective, coherence between practice and theory, valorization of the previous knowledge and of the culture of the students, and the developing of autonomy and consciousness. Paulo Freire isn´t against using technologies in education, but alerts that its thoughtless use might amplify inequality and promote and education that meets only capitalism’s interests and excludes the integral human being’s growth. Through this essay, it has been adressed fundamental aspects of Freire's pedagogy and its importance for the introduction of the new technologies on the educational process. Dialogue, critical developing, understanding of the historical process in a dialetic exercise are crucial points to techncology in school be an instrument in favor of knowledge building and transformation of the reality.